Heat transfer enhancement under turbulent flow for EG-water mixture of 40:60 ratio - Vandrangi, S.K. (Asian Research Publishing Network, 2016)
A theoretical model for the estimation of turbulent heat transfer has been developed employing the eddy diffusivity equation of Van Driest. Experiments have been undertaken for turbulent flow with Al2O3 nanofluid in base liquid Ethylene Glycol-water (EG-W) mixture of ratio 40:60 for a maximum concentration of 1.5 at a bulk temperature of 50 and 70°C. The numerical results for heat transfer are observed to be in good agreement with the experimental data with the nanofluid property equations developed. The maximum concentrations for which heat transfer enhancement can be attained are estimated to be 1.4 and 2.05 at 50 and 70°C respectively under turbulent flow. © 2006-2016 Asian Research Publishing Network (ARPN).